MEMBANGUN BUMDes YANG TANGGUH: PERAN STUDI KELAYAKAN DAN PENDAMPINGAN AKUNTANSI PERPAJAKAN DALAM REVITALISASI BUMDes DESA PEMUDA - Sari, Annisa; Yuswanita, Lativa; Suprayitno, Nur Fadillah; Trimuliani, Diva; Baharuddin, Kurniawan Harminsyah (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This community service program was implemented to address three critical challenges facing the BUMDes (Village-Owned Enterprise) in Pemuda Village, Tanah Laut Regency: (1) the absence of business feasibility studies, (2) limited accounting capacity, and (3) suboptimal tax understanding. Using a contextualized community training approach, the service team conducted three intervention modules: taxation counseling (PP 23/2018), business feasibility study workshops, and accounting training based on SAK EMKM (SME Accounting Standards). The results showed significant improvement in fiscal literacy (understanding corporate taxpayer status and the final income tax mechanism for SMEs), feasibility study preparation skills (production cost analysis and business unit break-even point calculation), and basic accounting skills. Operational outputs included business plan documents, bookkeeping training, and a fiscal calendar. A low-tech adaptation strategy successfully overcame digital infrastructure limitations through offline solutions and knowledge transfer agents. The conclusion confirms the effectiveness of the integrative "Tax-Feasibility-Accounting" training model with a contextual approach. Strategic recommendations include: (1) immediate implementation of feasibility documents by the Village Government, (2) module development by universities, and (3) digital infrastructure support from the local government. This program offers a replicable framework for strengthening rural BUMDes based on peer-to-peer learning